Catalytic biomass gasification of sawdust: integrated experiment investigation with process modeling and analysis. (21st March 2022) - Lan, Weijuan; Ding, Huiling; Jin, Xin; Yin, Dongxue; Wang, Yingxian; Ji, Jiangtao
Abstract: This paper reports on the investigation of the gasification from biomass using a laboratory scale fluidized bed gasifier. Main influencing factors, such as the temperature, steam flow rate and CaO to biomass mass ratio were studied. A model was developed for hydrogen-rich gas production from biomass via using ASPEN PLUS software. Sawdust was used as raw material for this study. Different operating conditions were considered and the model was verified. The results showed that the production of H2 and CO2 increased while the production of CO and CH4 decreased with increasing temperature. When the steam was used as the gasifying agent at different temperatures, the production of H2 increased significantly and its growth rate was 48%. The increase of CaO to biomass mass ratio from 0% to 50% resulted in hydrogen content increasing from 40% to 68%. Simulation results showed that the model was suitable for biomass gasification process, which could provide some reference value for further biomass gasification experiment.